2014
DOI: 10.1177/1352458514543732
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the World Health Organization Disability Assessment Schedule II (WHODAS-II) in patients with multiple sclerosis

Abstract: The WHODAS-II is a reliable and valid instrument for the assessment of patient-reported disability in MS, with some limitations including some item redundancy and questionable reliability of some subscales.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 24 publications
5
31
0
Order By: Relevance
“…Physician scored and patient‐reported disability measures were assessed including both physician‐derived EDSS and patient‐reported telephone EDSS score adapted for digital questionnaire use . For potentially more patient‐focused real‐life outcomes we used the WHODAS 2.0, which includes six domains of function: cognition, mobility, self‐care, interacting with other people, life activities, and participating in community activities …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Physician scored and patient‐reported disability measures were assessed including both physician‐derived EDSS and patient‐reported telephone EDSS score adapted for digital questionnaire use . For potentially more patient‐focused real‐life outcomes we used the WHODAS 2.0, which includes six domains of function: cognition, mobility, self‐care, interacting with other people, life activities, and participating in community activities …”
Section: Methodsmentioning
confidence: 99%
“…3 For potentially more patient-focused real-life outcomes we used the WHODAS 2.0, which includes six domains of function: cognition, mobility, self-care, interacting with other people, life activities, and participating in community activities. 4…”
Section: Clinical Measurementsmentioning
confidence: 99%
“…The WHODAS questionnaire showed suitable internal consistency to be used with DM patients in almost all domains, as other studies with similar Cronbach alpha coefficients have shown 18,19 . The only exception was in the Good relationship with people domain, in which, as other studies demonstrate [20][21][22] , the sexual activities question decreased the internal consistency of the domains. Therefore, the use of this question is debatable, as its advantages and disadvantages should be considered for the questionnaire's internal consistency.…”
Section: Discussionmentioning
confidence: 67%
“…17 The WHODAS-II was also translated and validated for the Italian healthy population. 18 More recently, its validity has been confirmed with modern Rasch model analyses in MS. 19 The WHODAS-II covers six domains of functioning: cognition (understanding and communicating), mobility (moving and getting around), self-care (hygiene, dressing, eating and staying alone), getting along (interacting with other people), life activities (domestic responsibilities, leisure, work and school) and participation (joining in community activities). Seven scales can be derived from the six domains of functioning: understanding and communicating (six items), getting around (five items), self-care (four items), getting along with others (five items), life activities: household (four items), life activities: work/school (eight items) and participation in society (eight items).…”
Section: Methodsmentioning
confidence: 84%